SIFAT KEPRIMAAN MODUL SEDERHANA CHEN UNTUK GRAF ????∞ - Risnawita Risnawita; Irawati Irawati; Intan Muchtadi Alamsyah (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2018)
Let ???????? be a field, ???????? is a directed graph. Let ????????~ is a directed line graph. Suppose that ????????[????????] is a class of Chen simple module for the Leavitt path algebra (???????????????? (????????)), with [p] being equivalent classes containing an infinite path. An infinite path p is an infinite sequence from the sides of a graph. In this paper it will be shown that ????????[????????]is not a prime module of the Leavitt path algebra for graph ????????∞ .Keywords : Leavitt path algebra, Graph ????????~, Chen simple modules, Prime modules